Resenha - The Entrepreneurial State: Debunking Public vs Private Sector Myths - Hamberger, Paula Andréa do Valle (Revista Economia Ensaios, 2014)
Resenha - The Entrepreneurial State: Debunking Public vs Private Sector Myths